Peningkatan Karakter Kemandirian Peserta Didik melalui Model Pembelajaran Contextual Teaching and Learning pada Pembelajaran IPA - Mulyani, Dewi; Kurnia, Ira Restu (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
This research is motivated by the low independence of students. One effort to overcome this problem is by using the Contextual Teaching and Learning learning model. The results of observations made on fourth grade students at SD Negeri Sukaresmi 06 show low independence. These results were obtained from several observations before this research took place, while this study used classroom action research methods, the subjects of this study were fourth grade students at SD Negeri Sukaresmi 06 Cikarang Selatan. The results of the study in cycle I meeting 1 showed 36.58% of students who showed independence in cycle I meeting 2 showed 51.21% of students who showed independence, while in cycle II meeting 1 showed student independence of 85.36% and in cycle II meeting 2 shows the independence of students by 95.12%. Based on these data, it is proven that Contextual Teaching and Learning can increase the independence of students.